PERANCANGAN SISTEM INFORMASI MANAJEMEN LOGISTIK OBAT MASUK DAN OBAT KELUAR - Iqbal Dzulfiqar Isakandar; Nazhua Puput Syaharani; Iqbal Dzulfiqar Iskandar; Imam Amirulloh (Yayasan Pendidikan Cahaya Budaya Indonesia, 2026)
PT AAN is a pharmaceutical distribution company that still relies on a manual record-keeping system using physical logbooks and Excel files. This practice has led to a high risk of data inaccuracies, shipping delays, and difficulties in real-time inventory tracking. This study aims to design a web-based Monitoring System for Incoming and Outgoing Drug Distribution to enhance efficiency, accuracy, and real-time oversight in the company's pharmaceutical logistics management. The system was developed using a prototyping approach, which encompasses requirement analysis, conceptual design using Unified Modeling Language (UML) modeling, prototype construction, system evaluation, and functionality testing using the Black Box Testing method. The design results demonstrate that the proposed system successfully maps two main user roles (Admin and Warehouse Staff) with features for automatic stock validation and data redundancy elimination, while achieving a 100% success rate in interface functionality testing via the Black Box method. In conclusion, the implementation of this web-based monitoring system design provides a significant contribution by minimizing human errors, accelerating distribution workflows, and optimizing the accuracy of month-end stock reporting at PT AAN.